ANALISIS PERAN EKONOMI KREATIF DALAM MEMAJUKAN USAHA MADU RUMAHAN DI KAMPUNG MADU PANGANDARAN - Fitriya; Handayani, Dea (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Creative economy is a new economic concept based on new things that can produce a new and creative idea in a process of creating a product or service. This is also driven by the advancement of information and communication technology which is developing very quickly. This study aims to analyze the role of the creative economy in advancing the home-based honey business in the Pangandaran Honey Village. The research method used is descriptive method, through literature study. The results of the study indicate that technological developments are used to develop businesses, both in the production process, promotion, and sales which have succeeded in making this business progress and develop rapidly. This case can happen because of a change from a conventional process to a modern one. Along with the development of this business, it is hoped that it can help the economic conditions of entrepreneurs and the surrounding community become better and can open up new job opportunities. By utilizing technology and the role of the creative economy, it is hoped that it will have a positive impact on the progress of this home-based honey business so that it can be more widely known both nationally and internationally.